Theoretical Study: The Diffusion of "Piknet" Innovation Sound Wave Attractor In Bulak District, Surabaya - Rosana, Nurul; Harahab, Nuddin; Ciptadi, Gatot; Kurniawan, Andi (Technium Social Sciences Journal, 2021)
Diffusion of innovation is a process which needed in an effort to adapt to an idea or technology so that a person or group of people can adopt a new subject through the stages set. The purpose of this research is to hope that the process of accepting the attractor based on the "Piknet" sound wave as an innovation can be studied based on the diffusion theory of innovation from Rogers. The method used in this research is a literature review which was carried out for 2 (two) months, in June and July 2021. The object of the writing is to deepen Rogers’ theory of the diffusion of innovations that can be used as a basis for determining the stages of the wave-based attractor diffusion process. the sound of "Piknet" to groups of fishing fishermen in Bulak District, Surabaya. Rogers’ innovation diffusion theory can be used as the basis for the diffusion process of "Piknet" sound wave-based attractor innovation in Bulak District, Surabaya, using elements and stages of the decision process that are adapted to the conditions of the local community.